Study of socio-environmental vulnerability indicators of communities neighboring Mineradora Vale Verde, Municipality of Craíbas/AL (Research, Society and Development, 2021)
The Alagoas reserve, known as Serrote da Laje, located in the center of Alagoas,in Craíbas city, is part of the four districts with cupriferous mineralizations in Brazil, which characterizes the possibility of territorial growth and development,  but it can also cause damage and further accentuate fragility in the region. Therefore, the main aim of the research is to drawing a social, economic and environmental profile using indicators to assess the vulnerability of communities in the vicinity of Mineradora Vale Verde. Thus, it is necessary to determine the vulnerability of localities and implement sustainability indicators in the surrounding regions, in this way, identifying the weaknesses of the communities and the consequences arising from the installation of the mining company, whether positive or negative. Wherefore, it is necessary to create a database in which it will be used in the future to identify whether Mineradora Vale Verde is providing a healthy development with the communities. It is expected that this research will contribute to help in the solution of these fragilities.